Kidney and Urinary Tract Involvement in Chronic Myelomonocytic Leukemia - Rose Mary Attieh; Farhana Begum; David Chitty; Hassan Izzedine; Kenar D. Jhaveri (Kidney Medicine, 2024)
Chronic myelomonocytic leukemia (CMML) is a hematologic malignancy affecting the bone marrow and resulting in peripheral blood monocytosis. Kidney and urinary tract involvement is common and can present dramatically with life-threatening consequences. Kidney involvement can be the result of direct or indirect mechanisms, including prerenal azotemia, glomerular disease, tubulointerstitial involvement, and renovascular disorders. Urinary tract involvement, electrolyte and acid-base disorders, as well as nephrotoxicity from treatment of the disorder can also occur. Given this multifactorial pathogenesis involving several mechanisms concomitantly, nephrologists must exercise heightened awareness and maintain a low threshold for kidney biopsy. There is a pressing need for future research endeavors to elucidate and target the manifestations of CMML that involve the kidneys with the ultimate goal of augmenting overall prognosis and therapeutic outcomes.